Latinas: life histories and the factors that influence success - Gallegos, Loretta E., author; Lehmann, Jean P., advisor; Banning, James H., committee member; Davies, Timothy Gray, committee member; Valdez, N., committee member (Colorado State University. Libraries, 2006)
This ethnographic study identifies the factors and actions that influence the success of Latinas born and raised in the United States and living in the Rocky Mountain Region. In the context of this study, Latina is a nomenclature used interchangeably with Chicana, Hispanic, and Mexican-American. The participants have achieved advanced degrees and are in positions of leadership. They are first generation college graduates who come from working class families. An emancipatory paradigm, a parallel concept to qualitative design, is the overall approach to this study which addresses social oppression at any level of occurrence. Participants' experiences are relayed through narrative life histories and further displayed using within-case analysis and cross-case analysis to present the research findings and themes. The foremost themes that emerged from this study were identified as career, family, economic, and educational systems, ethnic identity, and resiliency. Within each of these major themes are numerous support themes that collectively illustrate the factors that contribute or hinder the advancement of Latinas. The support themes within the concept of career are leadership style, barriers to career, career mentors, and entrepreneurship. The support themes within the concept of the family system are the family unit, traditions, work ethic, and family resiliency. The support themes within the concept of the economic system are the issues surrounding poverty and class division. The educational system illustrated multiple support themes within parental influence, the educational environment in the elementary, secondary, and college experiences, barriers to education, and mentors in education. The support themes within the concept of ethnic identity presented issues in childhood, adolescence, adulthood, and defining community. The support themes within the concept of resiliency produced information on significant life events, personality traits, and personal work ethic. The findings suggest evidence that strong family support and positive ethnic identity are among the key factors that attributes to the success of Latinas.
Keywords: higher education; social studies education; cultural anthropology